2014
DOI: 10.12717/dr.2014.18.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Spawning Behavior, Egg Development, Larvae and Juvenile Morphology of Hyphessobrycon eques (Pisces: Characidae) Characidae Fishes

Abstract: Hyphessobrycon eques is a famous fish for ornamental fish market and aquarium. They are inhabit in regions of Amazon and Paraguay River basin. Serpae fishs were investigated 2-3 males are chased to female, and then males attempted to simulate the females abdomen. After fertilization, eggs were kept in incubators at 28 o C. The fertilized eggs had adhesive and demesal characteristics and had a mean diameter of 0.92 ± 0.01 mm. Larvae hatched at 16 hrs post fertilization. The hatched larvae averaged 2.90 ± 0.16 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 10 publications
2
35
0
Order By: Relevance
“…In another study (Cole & Haring, ), it was reported that Hyphessobrycon serpae (Characidae) eggs were in the range of 0.74–0.90 mm in diameter. The diameter of the eggs of serpae tetra, investigated in this study, was reported to be around 0.92 ± 0.01 mm and in the range of 0.91–0.93 mm (Park et al, ). The diameter of the eggs of Hyphessobrycon anisitsi , a species close to serpae tetra, was reported to be close to these species (average 0.74 ± 0.07 mm; in the range of 0.63–0.91 mm; Park, Han, & Han, ).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…In another study (Cole & Haring, ), it was reported that Hyphessobrycon serpae (Characidae) eggs were in the range of 0.74–0.90 mm in diameter. The diameter of the eggs of serpae tetra, investigated in this study, was reported to be around 0.92 ± 0.01 mm and in the range of 0.91–0.93 mm (Park et al, ). The diameter of the eggs of Hyphessobrycon anisitsi , a species close to serpae tetra, was reported to be close to these species (average 0.74 ± 0.07 mm; in the range of 0.63–0.91 mm; Park, Han, & Han, ).…”
Section: Discussionmentioning
confidence: 68%
“…It also reported that the first horizontal cleavage occurs between the 32 and the 64 cell stages in the Atlantic cod Gadus morhua (Hall, Smith, & Johnston, ) in the Cichlasoma dimerus (Meijide & Guerrero, ); and in the zebrafish Danio (Brachydanio) rerio (Kimmel et al, ) at the sixth cleavage. In a study conducted on developmental morphology of embryonic and larval stages of serpae tetra (Pisces: Characidae; Park et al, ), embryonic development periods of fertilized eggs kept at 28°C water temperature were reported. According to Park et al (), embryonic development stages are defined in one‐hour or half‐hour periods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations